A new species of Omaliopsis Jeannel, 1940 (Coleoptera: Omaliinae: Omaliini) from Nepal, and new records from Eastern Palaearctic region - Shavrin, Alexey V. (Zootaxa, 2025)
Shavrin, A.V. (2019) Three new species and a new combination in the genus Omaliopsis Jeannel, 1940 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) of China and Nepal. Zootaxa, 4603 (2), 354–364. https://doi.org/10.11646/zootaxa.4603.2.8 Shavrin, A.V. (2023a) Four new species of the genus Omaliopsis Jeannel, 1940 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) of China. Zootaxa, 5380 (5), 446–460. https://doi.org/10.11646/zootaxa.5380.5.2 Shavrin, A.V. (2023b) Three new species of Omaliopsis Jeannel, 1940 and Omalium Gravenhorst, 1802 from Taiwan (Coleoptera: Staphylinidae: Omaliinae, Omaliini). Zootaxa, 5244 (2), 173–181. https://doi.org/10.11646/zootaxa.5244.2.5 Shavrin, A.V. (2024) A new species of the genus Omaliopsis Jeannel, 1940 from eastern Nepal (Insecta: Coleoptera: Staphylinidae: Omaliinae: Omaliini). In: Hartmann, M., Barclay, M. & Weipert, J. (Eds.), Biodiversität und Naturausstattung im Himalaya VIII. Verein der Freunde und Förderer des Naturkundmuseums Erfurt e. V., Erfurt, pp. 299–302.